481 EXPRESSION OF ANDROGEN RECEPTOR AND HER 2/NEU IN ESOPHAGEAL SQUAMOUS CELL CARCINOMA AND ITS MICOENVIRONMENT. (14th September 2020) - Surana, R; Rajendran, R; D, D; Rajendran, S; Chandramohan, S
Abstract:  : Esophageal cancer (EC) is the sixth most common cause of cancer-related deaths. Esophageal squamous cell carcinomas (ESCCs) have a higher incidence and worse prognosis in males, which may be dependent on the difference of environment of sex steroids. The influence of androgen receptor (AR) and HER 2/neu expression on hormone-related cancers are well known but their role in EC shows conflicting data. This warrants further investigation on their influence on tumor microenvironment of EC. Methods: All the cases of biopsy proven primary ESCC which presented to the institute in the years 2016–2020 were included. Patients undergoing neoadjuvant therapy were excluded. Epidemiological and pathological data were noted from the patient records. Paraffin embedded tissue samples of the patient were collected and immunohistochemical staining (IHC) for AR and HER 2/Neu was performed. The stained slides were then scored independently by three pathologists. Scoring criteria: AR nuclear staining of ≥5% of the lesional cells were considered positive. Cells showing weak to strong complete/basolateral/lateral membrane staining in ≥5 cell groups were scored positive for HER 2/neu. Results: The study included 24 individuals, 16 males and 8 females with esophageal SCC. The tumor cells showed AR positivity in 12.5% and HER 2/neu positivity in 16.67% of the tissue samples by IHC. There was no significant gender difference in the expression of AR and HER 2/neu in this study. In addition AR expression was seen in 41.67% (N = 10) of adjacent stromal cells (in 66.67% (2 of 3) of the AR positive and 38.09% (8 of 21) of the AR negative specimens) with a p value of 0.028 (p < 0.05). There was no significant variation by gender. Conclusion: There was a statistically significant expression of AR in the stromal cells of both AR positive and negative tumors. AR expression has been reported in the stroma of esophageal adenocarcinoma which was attributed to paracrine effects following androgen stimulation. To our knowledge, this is the first report of AR expression in the tumor microenvironment of esophageal SCCs. This study is limited by the small sample size and warrants further research.